(3CQLhRI aj GdWHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3BNQgG (B:s
(3eHJhQ GdBNQ jfJgi eG ajgG CKfGA GdcdGe Ydi YdGL GdNdY ai GdYXe hBNQ eG ajgG (B: (3hbO aQZJ ef LejY GdYed hGdBf CbWY Hbhd eced s
(3Vef eLehY , JQJjHgG (B: (3ef U (B34 - (3U(B74s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH (B- (3U (B15 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs